2008
DOI: 10.1016/j.jns.2008.01.016
|View full text |Cite
|
Sign up to set email alerts
|

A novel tRNAVal mitochondrial DNA mutation causing MELAS

Abstract: Mitochondrial encephalopathy, lactic acidosis and stroke-like episodes (MELAS) is the most common mitochondrial disease due to mitochondrial DNA (mtDNA) mutations. At least 15 distinct mtDNA mutations have been associated with MELAS, and about 80% of the cases are caused by the A3243G tRNA(Leu(UUR)) gene mutation. We report here a novel tRNA(Val) mutation in a 37-year-old woman with manifestations of MELAS, and compare her clinicopathological phenotype with other rare cases associated tRNA(Val) mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
25
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 22 publications
1
25
2
Order By: Relevance
“…In accordance with these three reported cases, our two patients developed cardiac conduction abnormalities and hypertrophic cardiomyopathy within a neurological presentation, and because of this, together with radiographic findings, MD was suspected in both cases. Muscle biopsies did not confirm the clinical impression of MD as they were morphologically and histochemically normal in the two patients, in contrast with biopsy findings of patients with mutations in the MT-TV gene previously described (Chalmers et al, 1997;Tiranti et al, 1998;Sacconi et al, 2002;McFarland et al, 2002;Tanji et al, 2008;Horváth et al, 2009;Yan et al, 2010). On the other hand, biochemical analysis showed a decrease in MRC complex I activity in muscle homogenate from patient 1, and a combined deficiency in the activity of MRC complexes I and IV from patient 2, as in most previous reports on mutations in the MT-TV gene (Chalmers et al, 1997;Tiranti et al, 1998;Sacconi et al, 2002;McFarland et al, 2002;Tanji et al, 2008;Horváth et al, 2009;Yan et al, 2010).…”
Section: Discussioncontrasting
confidence: 86%
See 2 more Smart Citations
“…In accordance with these three reported cases, our two patients developed cardiac conduction abnormalities and hypertrophic cardiomyopathy within a neurological presentation, and because of this, together with radiographic findings, MD was suspected in both cases. Muscle biopsies did not confirm the clinical impression of MD as they were morphologically and histochemically normal in the two patients, in contrast with biopsy findings of patients with mutations in the MT-TV gene previously described (Chalmers et al, 1997;Tiranti et al, 1998;Sacconi et al, 2002;McFarland et al, 2002;Tanji et al, 2008;Horváth et al, 2009;Yan et al, 2010). On the other hand, biochemical analysis showed a decrease in MRC complex I activity in muscle homogenate from patient 1, and a combined deficiency in the activity of MRC complexes I and IV from patient 2, as in most previous reports on mutations in the MT-TV gene (Chalmers et al, 1997;Tiranti et al, 1998;Sacconi et al, 2002;McFarland et al, 2002;Tanji et al, 2008;Horváth et al, 2009;Yan et al, 2010).…”
Section: Discussioncontrasting
confidence: 86%
“…In an attempt to identify mtDNA mutations associated with MCMs, we performed a systematic search in a series of patients that were suspected of MCM. As a result of this study, two transitions in the MT-TV gene were identified, the putative m.1628C>T mutation and the previously described, but not functionally characterized, m.1644G>A sequence variation (Tanji et al, 2008). In the present report, a selective reduction of the steady-state mt-tRNA Val level in the patient harbouring the m.1644G>A transition was found, confirming both the cardiac and the neurological involvement of this mutation.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…Studies have shown that the mutational spectrum is broad. About 80% of MELAS patients exhibit a heteroplasmic mutation in the dihydrouridine loop of the tRNA Leu (UUR) gene at nucleotide position 3243 [21] . Another T-to-C transition at nucleotide position 3271 occurred as a secondary common mutation [3] .…”
Section: Ischemic Strokementioning
confidence: 99%
“…Research on the DNA damage and repair pathway [90] , cytochrome P450 [91] , COX-2 [92] , and endothelial nitric oxide synthase (eNOS) [21] in ischemic stroke has been reported; however, there was no reliable evidence of association, and further studies thus are required.…”
Section: Other Candidate Pathways and Genesmentioning
confidence: 99%